Memahami Metode Dan Media Pembelajaran Dalam Perspektif Islam - M Yunus Abu Bakar; Muhammad Jawad Attaqy; Irji’i Ahmad Fahresi; Muhammad Nerikhul Amin (Journal of Cultural Relativism (JCR), 2024)
This article discusses the important role played by learning approaches and resources in Islamic education. In the current era of globalization, the problem of Islamic education is increasingly difficult due to the rapid growth of technology and information. Therefore, it is very important to have a deep understanding of how Islam can implement effective learning approaches. Islamic education includes the development of morality, wisdom, and spirituality in addition to acquiring knowledge. This article begins by discussing the concept of education in Islam, emphasizing the importance of education as a way to achieve truth and perfection in life. In addition, we study the Islamic values ​​that underlie learning, such as respect, justice and responsibility. Next, we study various educational approaches that are in line with Islamic principles, such as cooperative, active, and experience-based learning. A deep understanding of Islamic learning approaches and media enables educators to create more meaningful and relevant learning experiences for Muslim students. It is hoped that this will help prepare a generation of Muslims who are intelligent, knowledgeable, and able to contribute positively to global society.